2013
DOI: 10.1249/mss.0b013e31829a6ce8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Responsiveness in Metabolic Syndrome after Eight Weeks of Cycle Training

Abstract: Introduction Insulin resistance in obesity is decreased after successful diet and exercise. Aerobic exercise training alone was evaluated as an intervention in subjects with the metabolic syndrome. Methods Eighteen non-diabetic, sedentary subjects, eleven with the metabolic syndrome, participated in eight weeks of increasing intensity stationary cycle training. Results Cycle training without weight loss did not change insulin resistance in metabolic syndrome subjects or sedentary control subjects. Maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 39 publications
5
33
0
Order By: Relevance
“…These observations corroborated the results of Gomes et al, showing that exercise ameliorated insulin hypersecretion from pancreatic islets of HF diet rats [38]. An increased GLUT4 expression was also observed in trained subjects with MetS [39, 40] and could participate to the decreased glucose intolerance. These studies coupled with our results confirmed that physical activity provides numerous health-related benefits that prevent the development of MetS, whether directly through its effect on skeletal muscle and energy expenditure or indirectly by changing nutrition behavior.…”
Section: Discussionsupporting
confidence: 89%
“…These observations corroborated the results of Gomes et al, showing that exercise ameliorated insulin hypersecretion from pancreatic islets of HF diet rats [38]. An increased GLUT4 expression was also observed in trained subjects with MetS [39, 40] and could participate to the decreased glucose intolerance. These studies coupled with our results confirmed that physical activity provides numerous health-related benefits that prevent the development of MetS, whether directly through its effect on skeletal muscle and energy expenditure or indirectly by changing nutrition behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the present results are also somewhat similar to those showing that physical exercise causes weight-loss and reduces the incidence of Type 2 diabetes in overweight men with impaired glucose tolerance (Stuart et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The results are essentially similar to those from human studies in which physical exercise has invariable beneficial effects causing decreased in body weight and visceral fat accumulation in relatively short time intervals (Henriksen, 2002;Stuart et al, 2013). Furthermore, the present results are also somewhat similar to those showing that physical exercise causes weight-loss and reduces the incidence of Type 2 diabetes in overweight men with impaired glucose tolerance (Stuart et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations